Treatment Site Does Not Affect Changes in Pulse Wave Velocity but Treatment Length and Device Selection Are Associated With Increased Pulse Wave Velocity After Thoracic Endovascular Aortic Repair - Hori, Daijiro; Fujimori, Tomonari; Kusadokoro, Sho; Yamamoto, Takahiro; Kimura, Naoyuki; Yamaguchi, Atsushi (Frontiers in Physiology, 2021)
Background: Endovascular treatment of aortic aneurysm is associated with increase in pulse wave velocity (PWV) after surgery. However, effect of different types of endovascular devices on PWV at different sites of the thoracic aorta remains unclear. Objective: The purpose of this study was 1) to investigate the changes in PWV after endovascular treatment of thoracic aortic aneurysm; 2) to evaluate whether there is a difference in the changes in PWV at different treatment site; 3) and to evaluate the effect of treatment length on changes in PWV. Methods: From July 2008 to July 2021, 276 patients underwent endovascular treatment of true thoracic aortic aneurysm. Of these patients, 183 patients who underwent preoperative and postoperative PWV measurement within 1 year of surgery were included in the study. Treatment length index was calculated by treatment length divided by the patients’ height. Results: Five different types of endovascular devices were used. (Najuta, Kawasumi Laboratories, Inc. Tokyo, Japan; TAG, W.L. Gore & Associates, Inc. AZ, USA; Relay, Bolton Medical, Inc. FL, USA; Talent/Valiant, Medtronic, MN, USA; Zenith, Cook Medical, IN, USA). There was no significant change in PWV in patients receiving Najuta (Before: 2040±346.8cm/s vs. After: 2084±390.5cm/s, p=0.14). However, significant increase was observed in other devices: TAG (Before: 2090±485.9cm/s vs. After: 2300±512.1cm/s, p=0.025), Relay (Before: 2102±465.3cm/s vs. After: 2206±444.4cm/s, p=0.004), Valiant (Before: 1696±330.2cm/s vs. After: 2186±378.7cm/s, p<0.001), and Zenith (Before: 2084±431.7cm/s vs. After: 2321±500.6cm/s, p<0.001). There was a significant increase in PWV in patients treated from aortic arch (Before: 2006±333.7cm/s vs. After: 2132±423.7cm/s, p<0.001), and patients treated from descending thoracic aorta (Before: 2116±460.9cm/s vs. After: 2292±460.9cm/s, p<0.001). Multivariate analysis showed that treatment site was not an independent factor associated with changes in PWV. However, Najuta (Coef -219.43, 95%CI -322.684 to -116.176, p<0.001) and treatment index (Coef 147.57, 95%CI 24.826 to 270.312, p=0.019) were independent factors associated with changes in PWV. Conclusions: Najuta did not show significant increase in PWV while other commercially available devices showed significant increase. The treatment site did not have different effect on PWV. However, treatment length was an independent factor associated with increase in PWV.